Venture capital industry emergence and development in India and Brazil: the role of the state and challenges for the Global South countries - Gonzalo, Manuel; Guimaraes Alves, Nathalia; Federico, Juan; Szapiro, Marina; Kantis, Hugo (Innovation and development, 2024)
Most governments around the world are fostering innovation and entrepreneurial systems with a prominent role for venture capital (VC) support policies. However, the debate about the role and impact of VC support policies is still focused on the countries of the Global North. In this context, this paper seeks to describe and analyse the role that the state has played in the emergence and development of the VC industry in India and Brazil, two of the biggest economies of the Global South. We adopt a systemic and evolutionary perspective under the general context of a renewed role for the state in financing innovation. We offer interesting questions and implications to discuss the challenges, scale and impact that could be expected from VC industry support policies in the Global South countries.